Organic pest repellent - Engku Hadi, Tengku Muhammad Hafiz; Muhammad Sabri, Muhammad Adib; Ahmad Takri, Ahmad Azhari; Ismail, Salwani; Mat Rosid, Salmiah Jamal (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
The public's interest in environmentally sound pest control methods and the pest group's resistance to pesticides have recently driven the search for pesticides. In the home and city environment, parasites are mice, birds, insects, and other organisms that share their habitat with humans to feed and damage items. This pest control is carried out by exclusion, subtraction, physical removal or chemical means. Some pesticides not only harmful to cancer but also to human health, but can also harm wildlife. Therefore, an alternative organic pest repellent has been developed by using organic materials which were cinnamon and clove oil in order to make movement of insects outside the source of odor without direct contact and direct contact. The organic pest repellent (cinnamon and clove) was extracted using methanol solvent. The filtered extracts were then evaporate using centrifugal rotary evaporator to get the paste. This paste was mixed with a small amount of methanol. The results showed that, an ant is move away from the food that has been sprayed with organic pest repellent in the surrounding plate of food. This product is environmental friendly and chemical free for the usage in the household.